The deductive detective - Rock, Brian, 1966- (Sylvan Dell Publishing, 2013)
"Someone stole a cake from the cake contest--who could it be? Twelve animal bakers are potential suspects but Detective Duck uses his deductive reasoning skills to 'quack' the case"--